MODAL ANALYSIS OF THE FOUNDATION OF THE OVERPASS BRIDGE TYPE BY THE METHOD OF FINITE ELEMENTS - Petrenko, V. D.; Tiutkin, O. L.; Selikhova, T. O. (Science and Transport Progress, 2008)
The results of modal analysis of overbridge with investigation of forms and frequencies of foundation by the finite-element method are presented in the paper.